2021
DOI: 10.3390/w13111590
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Freshwater Eutrophication with Limited Limnological Data Using Artificial Neural Networks

Abstract: Artificial Neural Networks (ANNs) have wide applications in aquatic ecology and specifically in modelling water quality and biotic responses to environmental predictors. However, data scarcity is a common problem that raises the need to optimize modelling approaches to overcome data limitations. With this paper, we investigate the optimal k-fold cross validation in building an ANN using a small water-quality data set. The ANN was created to model the chlorophyll-a levels of a shallow eutrophic lake (Mikri Pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 64 publications
2
15
0
2
Order By: Relevance
“…Even a slight decrease in nitrogen contents in Lake Union improves lake trophic status, but adding nutrients to the lake promotes eutrophication. A recent study conducted by Hadjisolomou et al [34] in Lake Mikri Prespa (Greece) reported similar findings. Studies conducted by King County in both 2002 and 2014 have also reported that within saltwater intrusion, there were increases, among others, in the contents of nitrogen in lake water [35].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Even a slight decrease in nitrogen contents in Lake Union improves lake trophic status, but adding nutrients to the lake promotes eutrophication. A recent study conducted by Hadjisolomou et al [34] in Lake Mikri Prespa (Greece) reported similar findings. Studies conducted by King County in both 2002 and 2014 have also reported that within saltwater intrusion, there were increases, among others, in the contents of nitrogen in lake water [35].…”
Section: Resultssupporting
confidence: 66%
“…Deng et al [33] have successfully applied two different machine-learning methods (artificial neural networks and a support vector machine) to accurately predict algal growth and eutrophication in Tolo Harbour (Hong Kong). Hadjisolomou et al [34] have applied an artificial neural network to model the chlorophyll-a levels of a shallow eutrophic lake (Mikri Prespa, Greece), which is a crucial parameter for estimating CCME-WQI.…”
Section: Introductionmentioning
confidence: 99%
“…Prior modeling of HABs accommodating nonlinearity of relationships and non-normality of distributions has been undertaken by statistical regression models, and the power of machine learning techniques is beginning to be recognized [39]. Machine learning has become a powerful tool in water quality assessment, from freshwater to marine waters [93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…However, Shariq et al (2020) developed the gabion weir discharge model through flow conditions Kouadri et al (2021) used eight soft computing methods for prediction of a water quality index (WQI). The artificial neural network (ANN) created a model for the chlorophyll-a levels of a shallow eutrophic lake (Mikri Prespa) located in N. Greece (Hadjisolomou et al 2021). Forecasting the infiltration rate (IR) of treated wastewater (TWW) is essential in regulating clogging problems.…”
Section: Introductionmentioning
confidence: 99%